Facile Preparation of ZnO Nanoparticles and Ag/ZnO Nanocomposite and Their Photocatalytic Activities under Visible Light - Thi Anh Tuyet Pham; Van Anh Tran; Van Duong Le; Minh Viet Nguyen; Duc Duc Truong; Xuan Truong Do; Anh-Tuan Vu (International Journal of Photoenergy)
Zinc oxide (ZnO) has been known as an excellent photocatalyst for the degradation of a variety of organic pollutants under UV irradiation. This work describes a synthesis of ZnO nanoparticles via a facile precipitation method, and Ag was doped into Ag/ZnO nanocomposite to improve the photocatalytic degradation of BPA under visible light irradiation. The obtained ZnO nanoparticles were 20 nm in size and had a relatively high surface area and pore volume, 26.2 m2/g and 0.48 cm3/g, respectively. The deposition of Ag led to a decrease in the surface area, pore volume, and band gap energy (Eg) of ZnO nanoparticles. However, the photocatalytic activity of Ag/ZnO composite in the case increased. The performance of ZnO was compared with Ag/ZnO composites at the different molar ratios, and the kinetic reaction of BPA in these catalysts was investigated by the first-order kinetic model. The sample of Ag/ZnO-10 composite had the highest catalytic activity and showed the degradation efficiency, reaction rate, and degradation capacity of 100% in 120 min, 0.014 min-1, and 40 mg/g, respectively. In comparison, the effects of Ag/ZnO molar ratio, catalyst dosage, solution pH, and concentration of BPA on photocatalytic degradation were investigated. Additionally, the photocatalytic performance of Ag/ZnO-10 composite was evaluated by the degradation of other persistent organic compounds such as phenol, tartrazine, and methylene blue and compared to other catalysts in literature.